2008
DOI: 10.1136/ard.2008.097527
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies in the rheumatoid arthritis abatacept clinical development programme: an epidemiological assessment

Abstract: Objective:To provide context for the malignancy experience in the rheumatoid arthritis (RA) abatacept clinical development programme (CDP) by performing comparisons with similar RA patients and the general population.Methods:Malignancy outcomes included total malignancy (excluding non-melanoma skin cancer (NMSC)), breast, colorectal, lung cancers and lymphoma. Comparisons were made between the observed incidence in patients within the abatacept CDP and RA patients on disease-modifying antirheumatic drugs (DMAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 39 publications
(88 reference statements)
6
59
1
5
Order By: Relevance
“…The IR of overall malignancy reported in the ACQUIRE LTE study (1.19) is within the range of IR reported for cohorts of DMARD-treated patients with RA (0.67-1.77) 16 . The IR reported here with SC ABA for breast and lung cancers (0.17 and 0.10, respectively) were also within the range of IR reported for cohorts of DMARD-treated patients with RA (0.14-0.34, 0.09-0.26, respectively) 16 .…”
Section: Rheumatologysupporting
confidence: 52%
See 1 more Smart Citation
“…The IR of overall malignancy reported in the ACQUIRE LTE study (1.19) is within the range of IR reported for cohorts of DMARD-treated patients with RA (0.67-1.77) 16 . The IR reported here with SC ABA for breast and lung cancers (0.17 and 0.10, respectively) were also within the range of IR reported for cohorts of DMARD-treated patients with RA (0.14-0.34, 0.09-0.26, respectively) 16 .…”
Section: Rheumatologysupporting
confidence: 52%
“…The IR of overall malignancy reported in the ACQUIRE LTE study (1.19) is within the range of IR reported for cohorts of DMARD-treated patients with RA (0.67-1.77) 16 . The IR reported here with SC ABA for breast and lung cancers (0.17 and 0.10, respectively) were also within the range of IR reported for cohorts of DMARD-treated patients with RA (0.14-0.34, 0.09-0.26, respectively) 16 . The IR of different malignancies that occurred in the ACQUIRE LTE are also consistent with the IR reported for the pooled SC ABA clinical trial experience (0.46 for basal cell carcinoma, 0.16 each for breast cancer and squamous cell carcinoma of skin) 14 and the pooled IV ABA clinical trial experience (0.15 and 0.12 for lung and breast cancers, respectively) 15 .…”
Section: Rheumatologysupporting
confidence: 52%
“…Compared with the general population, patients with RA have an elevated risk of developing malignancies, specifically lung cancer and lymphoma 15,16 . An analysis of clinical trial experience with abatacept, encompassing~8400 person-years of exposure, showed that the observed incidence rates of total malignancy, breast cancer, and lymphoma compared with the DB period remained unchanged and that overall incidence rates of cancer were consistent with expectation based on comparator RA cohorts treated with DMARD 17 .…”
Section: Discussionmentioning
confidence: 82%
“…The contribution to the total exposure time for each patient ended at the first occurrence of the AE. SIR with 95% CI were calculated for hospitalized infections and malignancies for abatacept treatment versus comparator cohorts, adjusted for age and sex 23 . SIR (95% CI) were computed by dividing the observed numbers of events with abatacept in the cumulative treatment period by the expected numbers based on event rates in the comparator cohorts.…”
Section: Rheumatologymentioning
confidence: 99%